A novel design for the development of deployable benthic microbial fuel cells using PPy-Fe2O3 coated multi-anode system. (August 2022) - Prakash, Om; Mungray, Alka; Kumar Mungray, Arvind; Kumar Kailasa, Suresh
Graphical abstract: Highlights: A novel design was proposed for deployable BMFC reactor. PPy/Fe2 O3 was used a composite for anode modification. Stacking of small electrodes were successfully demonstrated. 1.5 mW was produced by combination of multi-electrode system. Voltage booster was circuited to uplift the voltage from 0.7 V to 4.57 V. Abstract: Benthic microbial fuel cells (BMFCs) provide a reliable option to replace toxic batteries for powering naval sensors. However, reliability can be increased by providing a stable architectural framework and electrode setup to increase the power by overcoming the existing resistances and limitations, which have already been mentioned in the works of literature. In this work, we have tried to shortlist the current problem by defining a new architectural framework and enhancing the power by designing a PPy-Fe2 O3 coated multi-electrode system while maintaining a low footprint. A deployable BMFC was tested as a potential power generation source in marine sediment. A tubular column consisting of anodes at different positions in a vertical manner was employed in the sediment. Performances of the developed BMFC were evaluated by measuring open circuit potential and power generation. Maximum power of 1.5 mW was obtained when the anodes were combined altogether. The experiment continued for two months without any extra supplements. A voltage booster was successfully designed using an integrated circuit that further enhanced the input voltage from 0.7 V to 4.57 V. This study can be implemented as a progressive approach to develop marine-based microbial fuel cells further.